Detection of potentially clinically relevant lung nodules with breath-hold CT compared to free-breathing CT in PET-CT in oncology patients and the value of MIP reconstructions - Alemany Montserrat; Sörensen Jens; Trampal Carlos; Hansen Tomas (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Background: The value of an additional thoracic breath-hold (BH) CT in PET-CT for detecting small nodules is controversial. Purpose: To determine the value of a BH-CT compared to the routinely used free-breathing (FB) CT, and the value of maximum intensity projection (MIP) technique in these two CT series for detection and its potential clinical relevance in staging of small lung nodules in oncology patients. Material and methods: This retrospective study included 200 patients from February to September 2016 who were referred for oncological FDG PET-CT. Thin slice (1.25 mm) and MIP (10 mm) images were analyzed for detection of small lung nodules (1-10 mm). Binominal test and descriptive statistics were analyzed.  Results: It was possible to evaluate 186 patients, with a mean age of 70.0 yrs ± 11.1 yrs, range 27-96 yrs, consisting of 84 females (mean age 68.5 yrs ± 12.2, 27-90 yrs) and 102 men (71.3 yrs ± 10.1, 27-96 yrs). In FB-CT, 393 nodules were detected in thin slice CT images, with MIP in 578. In BH-CT, 534 nodules were detected and 905 with MIP (p< 0,001). The extra detected nodules were considered as having a potential clinical relevance in 4.8% (9 of 186) of the patients. The total radiation dose from the routine PET-CT, including FB-CT, was 26 mSv and an additional 4 mSv from the BH-CT. Conclusion: An additional BH-CT in deep inspiration compared with FB-CT detects more small lung nodules, which potentially could alter the TNM stage.